Factors influencing self-reliance in rice production, the case of small farmers in Bataan, Philippines - Abas, M. S. (International Journal of Agricultural Technology, 2016)
The study was intended to determine the factors influencing small farmers’ self-reliance in rice production that would enhance the respondents’ productivity without bringing harmful effects on the ecological system but rather for a sustainable agriculture. It was conducted in selected barangays of Bataan, Philippines with a total sample of 360 small farmer-respondents selected through stratified random sampling. Primary data were collected during the harvest seasons of the year 2011-2012 through structured interview involving farmers’ level of self-reliance and the factors influencing the respondents’ self-reliance. Descriptive and multiple regression analyses were employed to analyze the collected quantitative data. The findings revealed the following: 1) Farmers’ level of self-reliance was generally high on the aspects of state of mind, social and economic affairs while moderate on the aspects of technology management and natural resource management. 2) Multiple regression analysis showed that educational attainment, household size, number of crops, managerial subsystem, use of own seeds, use of organic fertilizer and farm work were the factors influencing the respondents’ self-reliance. Based on the results of the study, the number of crops is found to be the highest predictor variable that significantly influencing farmers’ level of self-reliance. The research also provided recommendations for small farmers to enhance rice production through self-reliance on the aspects of state of mind, social affairs, technology management, natural resource management, and economic affairs.